Evaluation of Effectiveness of Lignosulfonate Application for Organic Coal-Water Fuel Rheological Properties Improvement; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Osipov V. Vitaliy; Larionov K. B. Kirill Borisovich; Matveev A. S. Aleksandr Sergeevich; Gromov A. A. Aleksandr Aleksandrovich (2016, 2016)
Title screen